Strategi Membangun Integritas Guru Pendidikan Agama Kristen: Sebuah Studi Persepsi Dosen STT Bethel Indonesia, Jakarta - Sirait, Jannes Eduard (SEKOLAH TINGGI AGAMA KRISTEN TERUNA BHAKTI, 2024)
This research is intended to find and describe appropriate and relevant strategies and follow appropriate principles in building the integrity of Christian religious teachers as teachers and heralds of the Kingdom of God. This research began with the erosion of teacher integrity in their professional duties. So, the main research problem is the decline in the integrity of Christian religious teachers in carrying out their work. The research uses literature data and field data. This research is qualitative-phenomenological. Data collection techniques were carried out through semi-structured interviews with predetermined research informants. They are the people who are considered the most knowledgeable and have the most information about teacher integrity. The research conclusion is that Christian religious teachers must consistently develop self-integrity and be sustainable. Increasing self-integrity can be achieved with five strategies, namely: understanding the urgency and importance of building the self-integrity of Christian religious teachers, following and establishing rules for building self-integrity, having the essential capital or ability to build personal integrity, and continuously increasing knowledge of hard skills and soft skills so that they are experts in their scientific competencies, building networks with people in the same profession is necessary. Abstrak Penelitian ini dimaksudkan untuk menemukan dan menguraikan strategi-strategi yang tepat dan relavan serta mengikuti kaidah-kaidah yang tepat dalam membangun integritas dari guru agama Kristen sebagai pengajar dan pewarta Kerajaan Allah. Penelitian ini berawal dari fenomena terjadinya erosi integritas guru dalam tugas profesi. Jadi, masalah utama penelitian adalah tentang kemerosotan integritas guru agama Kristen dalam melakukan pekerjaan. Penelitian menggunakan data-data literatur dan data lapangan. Penelitian ini adalah kualitatif-fenomenologi. Teknik pengumpulan data dilakukan melalui wawancara dengan model semiterstruktur kepada informan-informan penelitian yang sudah ditentukan. Mereka adalah orang-orang yang dianggap paling paham dan memiliki banyak informasi seputar integritas guru. Kesimpulan penelitian bahwa guru agama Kristen harus konsisten mengembangkan integritas diri dan berkelanjutan. Peningkatan self-integrity dapat dilakukan dengan lima strategi, yaitu: memahami urgensi dan kepentingan membangun integritas diri guru agama Kristen, mengikuti dan menetapkan kaidah-kaidah dalam membangun integritas diri, memiliki modal pokok atau kemampuan dalam membangun integritas diri, meningkatkan pengetahuan hard skill dan soft skill secara kontinyu sehingga ahli dalam kompetensi keilmuannya, dan membangun jejaring dengan orang-orang yang seprofesi.